In vitro characterization of a novel type of radiopaque doxorubicin-loaded microsphere - Pan, Feng; Schneider, Daniel; Ryschich, Eduard; Qian, Baifeng; Vollherbst, Dominik; Möhlenbruch, Markus Alfred; Kauczor, Hans-Ulrich; Sommer, Christof-Matthias; Do, Thuy (CardioVascular and interventional radiology, 2020)
To evaluate and compare the material characteristics of a novel type of radiopaque doxorubicin-loaded microsphere (V-100) with radiopaque and non-radiopaque doxorubicin-loaded microspheres.